VAN NIEKERK, M.G. Inventory of documents - VAN NIEKERK, M.G. (ARCA, 2018)
Information regarding the political situation from 1910 to 1960.
COVERAGE: 1910-1960; 0.30 metres
Keywords: VAN NIEKERK, M.G.; Politics; South Africa